Impact of artificial feeding on the developmental cycle of two triatomine species - Raquel Aparecida Ferreira; Ana Carolina Corrêa Nascimento; Natalya Lorena da Silva Santos; Liléia Gonçalves Diotaiuti; Eduardo Fernandes e Silva; Silvia Ermelinda Barbosa (PLoS ONE, 2025)
Background Live animals are the preferred food source for rearing and keeping triatomines in insectaries. However, there is an increasing demand for artificial feeding as an alternative method to using live animals. Despite this demand, scientific studies showing the viability of rearing triatomine colonies in insectaries with artificial feeding are still lacking. In this regard, we tested whether feeding triatomines with an artificial system affects different physiological and biological parameters during the insects’ development. Methodology/principal findings Three experimental groups were established for the species Triatoma infestans and Panstrongylus megistus. The insects were fed weekly and individually, with each group receiving different treatments, as follows: A) artificial feeding system with rabbit blood, B) live animal host, and C) alternating feeding (one week A and the next B). The groups were kept under the same environmental conditions and monitored daily. The parameters evaluated per instar and total cycle were the effect of the blood supply method on the insects’ developmental time, the association between feeding method and insect mortality, weight gain, and the number of feedings needed to trigger molting. The latter two were evaluated only in P. megistus. Conclusions/significance Sex did not influence the insects’ survival or weight gain. The biological cycle duration was shortest in insects fed on a live animal host, followed by the group fed alternately, and longest in those fed artificially. Panstrongylus megistus fed on an artificial system required more feedings to complete molting and gained less weight. The insect mortality rate was not influenced by the feeding method. This is the first study showing that artificial feeding conditions affect different physiological parameters in two triatomine species, questioning the viability of exclusive artificial feeding as a sustainable strategy in a laboratory environment.